Field Trial of Factors Associated With the Presence of Dead and Non-ambulatory Pigs During Transport Across Three Colombian Slaughterhouses - Romero, Marlyn H.; Sánchez, Jorge Alberto; Hernandez, Rick Obrian (Frontiers in Veterinary Science, 2022)
Transport by land is an essential component for the commercialization of fattening pigs and can have a negative impact on animal welfare. In slaughterhouses, the presence of dead and non-ambulatory animals is an indicator of poor welfare during transport. The objective of the study was to identify risk factors associated with the frequency of dead and non-ambulatory pigs during transport. A survey was conducted in three Colombian slaughterhouses. Data were collected from 372 batches (n = 18,437 gilts barrows) and transported directly from the farms to the slaughterhouses. Each truck was individually evaluated; a structured survey was administered to drivers, non-ambulatory and dead pigs on arrival were identified and blood samples were obtained from non-ambulatory pigs to assess physiological indicators of stress. Mortality rates per batch at arrival ranged from 0.08 to 0.17% and prevalence of non-ambulatory pigs per batch ranged from 0.84 to 1.37%.The results of the multilevel mixed effects linear regression model identified the following as risk factors associated with the frequency of total transport losses: truck speed (P = 0.04), distance (P < 0.01), transport time (P < 0.01), load size (P < 0.01) and the driver (P < 0.01) including the farm as a fixed effect. This study identified risk factors that increased the probability of total transport losses during land transport under Colombian commercial conditions. But more research that involves commercial drivers is needed to develop effective strategies to improve Colombian pig's transportation chain.